Light Emitting Diode Simulation using MATLAB for Visible Light Communication - Ravichandran, Devan; Joret, Ariffuddin (Evolution in Electrical and Electronic Engineering, 2024)
This work focuses on Visible Light Communication (VLC), which designs and optimizes LED-based communication systems utilizing MATLAB simulations and light-emitting diodes (LEDs) circuit. Designing  LED and photodiode circuits with components such as current-limiting resistors is the first step in this study. Then, LED brightness variations are used to encode digital information by combining ASK and PSK modulation. In evaluating the designed VLC system performance, signal of the designed photodiode circuit has been compared to the input signal of the designed LED circuit. Referring to PSK modulation signal as input signal of the VLC system, it requires setting signal parameters of the  amplitude and frequency, while for ASK modulation only includes adjusting the duration of the signal. Due to these modulation schemes and as an effective 2-bit and 4-bit data transfer, the study examines modulation situations focusing on amplitude, frequency, and signal statistics changes. The results reveal that intentional modifications to signal characteristics maximize data transport, demonstrating the circuits' flexibility to accommodate varying data sizes and modulation techniques.